NAVIGATING DIGITAL ASSESSMENT: TEACHER-IDENTIFIED CHALLENGES AND STRATEGIES IN USING WORDWALL IN EFL CLASSROOMS - Muhammad Ayyub Herianto; Abd Halim; Andi Anto Patak; Muh Tahir (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study investigates the challenges and strategies experienced by English teachers in utilizing Wordwall as a digital assessment tool in a rural junior high school in Indonesia. While digital platforms are increasingly integrated into English language teaching, their application in under-resourced environments poses unique complexities. Employing a qualitative descriptive method, the study draws on in-depth interviews with two English teachers from SMPN 1 Tinondo, Southeast Sulawesi. Data were analyzed thematically using Braun and Clarke’s framework, revealing three major findings. First, infrastructural barriers, including limited internet access, shared digital devices, and inadequate training, significantly constrained the optimal use of Wordwall. Second, despite these limitations, teachers acknowledged various pedagogical benefits, such as increased student motivation, interactive assessment experiences, and alignment with competency-based curriculum goals. Third, teachers demonstrated creative adaptation strategies, such as rotating device access, using group-based tasks, and modifying content formats to accommodate technical challenges. These strategies reflect a high degree of teacher agency in overcoming contextual constraints. The study contributes to the discourse on digital assessment in rural EFL contexts by highlighting not only the technological and pedagogical dimensions but also the socio-cultural factors that shape implementation. The findings offer valuable implications for teacher training, policy development, and digital tool design tailored to low-resource settings